A TOPSIS-Based Decision Support System for Thesis Title Recommendation: Design, Implementation, and Experimental Evaluation - Firdaus Firdaus; Ritna Wahyuni (ILKOM Jurnal Ilmiah, 2026)
Selecting an appropriate thesis title is a critical step that significantly influences the direction and quality of undergraduate research. However, students often face difficulties due to limited understanding of research domains, lack of structured guidance, and subjective decision-making processes. This study proposes a web-based Decision Support System (DSS) utilizing the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to recommend thesis titles based on multiple criteria. The dataset consists of 120 thesis titles collected from the Information Systems program at Putra Indonesia University YPTK Padang over the period 2019–2024. Data collection involved 10 lecturers and 20 students through questionnaires and interviews to determine the relative importance of four criteria: relevance, availability of references, level of difficulty, and innovation. The system was developed using Python (Flask) and evaluated through experimental scenarios using representative alternatives. The results show that the proposed system successfully generates consistent rankings, with the alternative “Designing Mobile Applications for Local MSME Mapping” achieving the highest preference value of 0.697. The findings indicate that the system effectively balances benefit and cost criteria, providing objective and transparent recommendations. This study contributes to the development of practical and implementable decision support systems in academic environments by integrating TOPSIS into an interactive web-based platform. The proposed approach demonstrates strong potential to improve the efficiency, consistency, and objectivity of thesis title selection, although further validation using larger datasets is recommended